2018
DOI: 10.15195/v5.a8
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality and the Persistence of Racial Economic Disparities

Abstract: More than 50 years after the Civil Rights Act, black-white family income disparities in the United States remain almost exactly the same as what they were in 1968. This article argues that a key and underappreciated driver of the racial income gap has been the national trend of rising income inequality. From 1968 to 2016, black-white disparities in family income rank narrowed by almost one-third. But this relative gain was negated by changes to the national income distribution that resulted in rapid income gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 69 publications
1
71
0
Order By: Relevance
“…5 By focusing on percentile ranks, we capture changes in the relative position of racial groups in the income distribution. As discussed in Bayer and Charles (2018) and Manduca (2018), trends in the absolute dollar magnitude of racial disparities depend upon both changes in ranks and the marginal distribution of income in each generation. We focus on ranks to separate the forces that affect racial disparities from forces that affect the income distribution more generally, such as skill-biased technical change.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…5 By focusing on percentile ranks, we capture changes in the relative position of racial groups in the income distribution. As discussed in Bayer and Charles (2018) and Manduca (2018), trends in the absolute dollar magnitude of racial disparities depend upon both changes in ranks and the marginal distribution of income in each generation. We focus on ranks to separate the forces that affect racial disparities from forces that affect the income distribution more generally, such as skill-biased technical change.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Alternatively, infant health inequality may have persisted or increased since 2010. Some scholars have linked increasing income inequality with increasing infant health inequality ( Elgar et al, 2015 ; Manduca, 2018 ; Olson et al, 2010 ). For example, Olson and colleagues ( Olson et al, 2010 ) found that income and income inequality (measured using the Gini coefficient) explained a substantial proportion of variation in rates of preterm birth, low-birth weight, and very low birth weight infants.…”
Section: Why Infant Health Trends May Be Changingmentioning
confidence: 99%
“…There is a sizeable body of research documenting the ways that racial inequality is manufactured not by racial minority groups’ inherent shortcomings, subpar cultural values, or genetic inferiority, but by public policy, educational institutions, labour markets, and other structures (Shapiro ; Stainback and Tomaskovic‐Devey ; Tyson ). This scholarship is echoed by (or in some cases done in concert with) researchers affiliated with think tanks and non‐profits such as Demos, the Economic Policy Institute, and the Center for American Progress (Manduca ; Sullivan et al ). Yet we still find that whites continue to stigmatize people of colour and attribute ongoing racial inequality to blacks’ genetic inferiority (Feagin and O’Brien ) and/or presumed cultural deficiencies (Bonilla‐Silva ), despite extensive evidence to the contrary.…”
Section: Destigmatizing People Of Colourmentioning
confidence: 99%